Avoiding chronic and transitory poverty: evidence from Egypt, 1997-1999 - Haddad, Lawrence J.; Ahmed, Akhter (International Food Policy Research Institute, 2002)
This paper uses a panel data of 347 households in Egypt to measure changes in household consumption between 1997 and 1999 and to identify causes behind the changes. Per capita consumption decreased for the households during this time and, while not dramatic, it occurred at all points along the distribution. Over the two-year period, the number of households that fell into poverty was over twice as large as the number of households that climbed out of poverty. About two-thirds of overall poverty was chronic (average consumption over time was below the poverty line), and almost half of all poor were always poor. We use quantile regression methods to identify the factors that explain total, chronic, and transitory poverty. While our analysis ably documents the extent of transitory poverty, it does not explain well the determinants of this type of poverty. The predominantly chronic nature of poverty in the sample, and our ability to identify associated characteristics, strengthens the case for targeting antipoverty interventions such as food subsidies.